Political and Security Dynamics of South and Southeast Asia - Singh, Daljit (Book collections on Project MUSE., 2007)
Security and economic imperatives are increasingly intertwining the destinies of Southeast Asia and South Asia, making it necessary for scholars on both sides to deepen their understanding of each other's regions. This collection of papers, first presented at a Dialogue between the Institute of Southeast Asian Studies in Singapore and the Observer Research Foundation of India in March 2006, provides perspectives from India and Singapore on some of the major security and political issues facin ...